#TITLE_ALTERNATIVE# - LISMAWATIE (NIM 24006022), KURNIA
In the context of local development, the Human Development Index (HDI) is stipulated as one of the parameters stated in the Basic Patterns of Local Development. This shows that HDI plays an important role in the management of local government. The HDI and other indicators of human development will become the key to the success of the implementation of the directed planning and development. The role of HDI as a development parameter will be more outstanding if it is equipped with the proper data base and calculation without distinguishing poor areas the rich ones so that the development planning is expected to well take the side of the community. HDI- which is a development parameter of an area – should positively correlate with the poverty condition of the area because an area having high value of HDI is expected to ideally have high quality of the life of its community as well. In other words; if HDI value is high, the level of poverty is low. The fact, however; says that number of HDI value does not guarantee the level of welfare of the community. One of the reasons is that the calculation of HDI value is based on the value of aggregate using the principle of the average value so that the inaccuracy of the calculation of HDI value occurs. A complete and accurate data system will give us chances to be mare studying various kinds of impacts and the implementation of the development program of the previous periods, which can then be input for planning the future development. The performance assessment of the development based on the HDI parameter has also been carried out in Pematangsiantar since 1999, and has been published since 2001. This research; therefore; is carried out to investigate the implementation of riel HDI calculation, to study the HDI condition, and to find out the correlation between the HDI calculation and the poverty condition in Pematangsiantar. The research method used is quantitative and qualitative. The former is applied to recalculate the HDI value using the calculation commonly used by Badan Pusat Statistik (BPS). The later is used as the supporting data for the quantitative method, and is based on descriptive explorative approach-carried out by both studying the documents and interviews. Document study is aimed at finding the written information on HDI, development and poverty, while the interview at extracting the validity of the information taken from the documents. Both ways; however; are carried out in the institutions related to the HDI calculation, development programs, and poverty issues. The will then explorative descriptively be analyzed. The results of the analysis indicate that there have been inconsistencies in the HDI calculation in Pematangsiantar, which is caused by the HDI calculation using different values of expenses per capita. The results of riel HDI show that the status of human development of middle class is worthy. The results on the correlation between HDI calculation and the poverty condition, show a negative correlation, which is caused by outstanding differences of buying capacities. This negative correlation is also indicated on the Minimum Wage Regional, the increase of the regional Minimum Income Regional and on the Domestic Product of Regional Brutto (PDRB)-the increase of the Net Regional Domestic Product per capita, which is not accompanied by the decrease number of poverty. Directed to improve poverty in the perspective of the increase of HDI in Pematangsiantar using the analysis of the HDI calculation and the existing condition of poverty should be based on three HDI indicators and be consistently in line with the vision and mission of the local government of Pematangsiantar. These strategies should be formulized as follows: supports from the local government by providing scholarships for members of poor families; community-based projects to accelerate the decrease of poverty through the education system directly related to job vacancies; policy changes on economy; by establishing the economy information system; by stimulating the establishment of community-based and informal economy activities; and the development of small, middle and home industries.